2019
DOI: 10.31224/osf.io/f28zk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonlinear numerical simulation of punching shear behaviour of reinforced concrete flat slabs with shear-heads

Abstract: This paper examines the structural response of reinforced concrete flat slabs, provided with fully-embedded shear-heads, through detailed three-dimensional nonlinear numerical simulations and parametric assessments using concrete damage plasticity models. Validations of the adopted nonlinear finite element procedures are carried out against experimental results from three test series. After gaining confidence in the ability of the numerical models to predict closely the full inelastic response and failure mode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They concluded that most of the design code underestimates punching shear strength of the concrete compared to the experimental results, except the Eurocode 2, which gave higher results than the experimental. Bompa and Elghazouli [9] examined the structural response of reinforced concrete flat slabs, provided with fully embedded shear-heads, through detailed three-dimensional nonlinear numerical simulations and parametric assessments using concrete damage plasticity models.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that most of the design code underestimates punching shear strength of the concrete compared to the experimental results, except the Eurocode 2, which gave higher results than the experimental. Bompa and Elghazouli [9] examined the structural response of reinforced concrete flat slabs, provided with fully embedded shear-heads, through detailed three-dimensional nonlinear numerical simulations and parametric assessments using concrete damage plasticity models.…”
Section: Introductionmentioning
confidence: 99%